Multistage Extraction of Star Anise and Black Pepper Derivatives for Antibacterial, Antioxidant, and Anticancer Activity - Li, Helin; Wu, Xiaoyu; Li, Xin; Cao, Xiaobing; Li, Yanjun; Cao, Huaru; Men, Yongzhi (Frontiers in Chemistry, 2021)
Recently, natural resources attracted considerable interest for their applications in food security and human health problems. Traditional natural spices, such as star anise and black pepper, played important roles in pharmaceutical and food industry due to their strong pharmacological activity, antioxidant potential and rare complications. In order to achieve biomasses from the natural product with multiple bioactivities, we developed the multistage extraction method to extract and separate various bioactive compounds from these natural plants. Our work demonstrated that various bioactive-rich extractives were achieved using steam distilled- or oxidative-extraction method with high extraction yields and purity. Furthermore, the extractives in each step can be used not only as bioactive compounds, but also as a resource to further prepare different derivatives during the next extractive step, providing biomass-saving to a great extent. The extractives obtained with high yields and purities (>82%) were identified by 1H NMR, 13C NMR, FTIR, UV-vis, fluorescence spectroscopy and high-performance liquid chromatography (HPLC). Moreover, these biomasses display potent antibacterial activities against some types of microorganisms such as S.aureus, S.pyogenes, E.coli and S.typhi with a lowest MIC of 400 µg/ml for the development of antibacterial agents, significant antioxidant activity as the natural antioxidant for enhancing food shelf-life, and excellent anticancer activity that induces significant cancer cell apoptosis. This work showed the different multistage extracts from natural products, which enable to be applied in the fields of the pharmaceutical industry and the food industry.